A Study of the Impact of Atmospheric Pressure in Eastern Qilian Mountains on Vertical Deformation at GNSS Stations. Issue 1 (July 2020) - Yang, Guolin; Sun, Xuexian; Liu, Tao; An, Xuwei; Zhang, Bo
Abstract: The change of the earth's surface environmental load is an important factor that causes the crustal short-term movement. The project address is in the eastern part of Qilian Mountain, and we take the crustal vertical deformation and gravity changes affected by load changes as the research object. Based on the crustal load deformation theory, we use the data of GNSS continuous reference stations and meteorological stations in the region to study the evolution between atmospheric load changes and vertical crustal movement in the region from 2012 to 2017. The results show that the atmosphere in the eastern part of the Qilian Mountains is affected by atmospheric load periodically and varies with the seasons. On average, atmospheric pressure is low in summer and high in winter, resulting in annual periodic crustal vertical deformation, while the crustal uplifts in summer and declines in winter. The crustal deformation in most areas is the largest around January and August, and there are certain differences in crustal deformation in different areas.